Radiation and chemical crosslinking of PVA/starch - NASCIMENTO, CARLOS E. (2020)
In attainment of superabsorbent polymers (SAPs) based on PVA [poly (vinyl alcohol)] and starch, two different crosslinking processes were utilized: use of glutaraldehyde and gamma- radiation, aiming at evaluating the best alternative for the SAPs formation. Polymer mixtures from PVA aqueous solutions and starch suspensions were crosslinked chemically and by radiation apart. For that, the radiation absorbed dose and the proportion of crosslinker were kept fixed, varying only the amounts of PVA and starch at diverse proportions. It was observed experimentally that the irradiated samples showed a better reaction control and purity, but lower crosslinking degree than that of glutaladehyde-crosslinked SAPs, thus resulting higher swellings for the former. The glutaraldehyde-crosslinked samples showed a higher range of degradability on TGA (thermogravimetric analysis) test due to the presence of residual HCl and glutaraldehyde in them. IR spectra absorption bands of the chemically obtained SAPs showed glutaraldehyde peaks, whereas these were absent in the irradiated materials. By these experiments, one concluded that increases of starch proportion lead to decreases of the SAPs swelling, probably due to higher hydrophobic characteristics of starch than those of PVA, despite some properties of the this having been improved.